The integrative bioinformatics approaches to predict the xanthohumol as anti-breast cancer molecule: Targeting cancer cells signaling PI3K and AKT kinase pathway - Gupta, Kartikey Kumar; Sharma, Kamal Kant; Chandra, Harish; Panwar, Himalaya; Bhardwaj, Nitin; Altwaijry, Najla A.; Alsfouk, Aisha A.; Dlamini, Zodwa; Afzal, Obaid; Altamimi, Abdulmalik S. A.; Khan, Shahanavaj; Mishra, Abhay Prakash (Frontiers in Oncology, 2022)
Background Breast cancer is the most common type of cancer in women, and vast research is being conducted throughout the world for the treatment of this malignancy by natural products using various computational approaches. Xanthohumol, a prenylated flavonoid, is known for its anticancer activity; however, the mechanism behind its action is still in the preliminary stage. Methods The current study aimed to analyze the efficacy of xanthohumol compared to the currently available anticancer drugs targeting phosphoinositide-3-kinase (PI3K), serine/threonine kinase (AKT) receptors, and human epidermal growth factor receptor 2 (HER2) for breast cancer treatment through in silico analysis. Results The result revealed that the target compound showed significant binding affinity to targets within the PI3K, AKT, and HER2 signaling pathways with a binding energy of −7.5, −7.9, and −7.9 kcal/mol, respectively. Further prediction studies were then made concerning this compound’s absorption, distribution, metabolism, and excretion (ADME) as well as drug-likeness properties, resulting in its oral bioavailability with only a single violation of Lipinski’s rule of five. Conclusions The finding revealed the ability of xanthohumol to bind with multiple cancer cell signaling molecules including PI3K, AKT kinase, and HER2. The current novel study opened the door to advancing research into the management and treatment of breast cancer.